Atmospheric Carbon Mineralization in an Industrial-Scale Chrysotile Mining Waste Pile - Nowamooz, A.; Dupuis, Christian; Beaudoin, G.; Molson, J.; Lemieux, J.; Horswill, M.; Fortier, R.; Larachi, F.; Maldague, X.; Constantin, M.; Duchesne, J.; Therrien, R. (American Chemical Society, 2018)
Copyright © 2018 American Chemical Society. Magnesium-rich minerals that are abundant in ultramafic mining waste have the potential to be used as a safe and permanent sequestration solution for carbon dioxide (CO2). Our understanding of thermo-hydro-chemical regimes that govern this reaction at an industrial scale, however, has remained an important challenge to its widespread implementation. Through a year-long monitoring experiment performed at a 110 Mt chrysotile waste pile, we have documented the existence of two distinct thermo-hydro-chemical regimes that control the ingress of CO2 and the subsequent mineral carbonation of the waste. The experimental results are supported by a coupled free-air/porous media numerical flow and transport model that provides insights into optimization strategies to increase the efficiency of mineral sequestration at an industrial scale. Although functioning passively under less-than-optimal conditions compared to laboratory-scale experiments, the 110 Mt Thetford Mines pile is nevertheless estimated to be sequestering up to 100 tonnes of CO2 per year, with a potential total carbon capture capacity under optimal conditions of 3 Mt. Annually, more than 100 Mt of ultramafic mine waste suitable for mineral carbonation is generated by the global mining industry. Our results show that this waste material could become a safe and permanent carbon sink for diffuse sources of CO2.